The paradox of policy competition: A simple post-Keynesian theory of how beggar-thy-neighbour FDI-led growth strategies work in principle but not in practice - Ryan Woodgate (PSL Quarterly Review, 2025)
In recent decades, governments around the world have increasingly used various forms of state aid to try to attract and retain the business activity of foreign-owned multinational corporations. Yet, in most cases, this “commercialisation of state sovereignty” (Palan, 2002) has failed to catalyse foreign investment and economic growth as intended. This paper seeks to understand the general failure of such commercialised state strategies, while also explaining how demand and income growth in some notable exceptions (e.g., Ireland and Singapore) can be understood. To this end, a simple demand-led framework is presented that suggests that foreign-targeted state aid may lead to beggar-thy-neighbour, FDI-driven growth in one economy if certain conditions are met, such as there being sufficiently little policy competition from other countries. It is argued that the exceptional cases tend to be the early movers and that state aid for the attraction of foreign multinationals is unlikely to be an effective growth strategy in the current environment of intense state competition.